Importancia de prácticas agroecológicas en el cultivo de papaya Carica papaya en el Ecuador - Vera Cedeño, Víctor Estiven (2024)
This document aims to illustrate the importance of agroecological practices in the cultivation of Carica papaya in Ecuador. Internally, papaya is of great economic and social importance in Ecuador, as it contributes to employment and the local economy. Given the need to reduce the adverse effects associated with the excessive use of pesticides and fertilizers, the adoption of agroecological practices for papaya crops in Ecuador may face several challenges. Some of the reasons include farmers' resistance to change, lack of access to training and resources to implement these practices, and economic pressures to maintain high levels of production. The importance of agroecological practices in the cultivation of papaya (Carica papaya) in Ecuador is an interesting topic that addresses fundamental aspects of sustainable agriculture and social well-being. This is essential in this context, as it promotes a sustainable approach to agriculture. These practices include integrated pest management, promoting biodiversity, efficient use of natural resources, and reducing the use of pesticides. All of this contributes to improving soil quality, maintaining fertility and reducing environmental impact. However, challenges and limitations to widespread implementation of these practices have been identified, including the need for training, access to resources, and institutional support. Despite these challenges, there are opportunities in the Ecuadorian papaya sector to promote and strengthen the adoption of agroecological practices at the national level through policies and measures that encourage the adoption of agroecological practices.